The Effectiveness of Web-Based Art Culture Multimedia in Cultural Arts Learning for Class VIII at Mts Negeri 1 Sidenreng Rappang - Adinda Salman; Abdul Kahar; Muhammad Takdir; Hasanuddin Hasanuddin (Universitas Muhammadiyah Enrekang, 2025)
This research examines the effectiveness of web-based Art Culture multimedia in enhancing cultural arts learning for eighth-grade students at MTs Negeri 1 Sidenreng Rappang. The study was conducted using an experimental approach with a one-group pretest-posttest design. The participants of the study were 31 students from class VIII.A, selected through random sampling. Data was collected through multiple-choice tests and questionnaires, aimed at evaluating students' learning outcomes, both in terms of learning completeness and the time efficiency in receiving the material. The results indicated a significant improvement in students' learning outcomes after the use of the multimedia Art Culture platform. The paired sample t-test showed a significant difference between the pretest and posttest scores, with a mean score of 45.80 for the pretest and 83.11 for the posttest. This suggests that the use of Art Culture multimedia is effective in improving students' understanding and engagement in cultural arts education. The findings of this research provide valuable insights into the integration of digital media in enhancing the learning process in schools.